Preparation and characterization of Carbon Nanotube/Graphite Nanofiber and Carbon Nanotube/Graphite Nanofiber/Metal Oxide (Metal = Zn and Fe) nanocomposites for supercapacitor application - Ramli, Nurul Infaza Talalah (2016)
The ever-increasing demand for energy storage devices have stimulated intensive efforts to search for better energy storage materials. The impetus of this work was to synthesis a new material for supercapacitor electrodes that can bridge the storage gap between battery and conventional capacitor. In this research work, the physicochemical and electrochemical properties of CNT/GNF nanocomposite for supercapacitor application were studied. The CNT/GNF hybrid nanocomposites with varying weight percentage (5-40 wt %) of CNTs addition were prepared by simple mixing technique that involves stirring and sonicating technique. The performance of the optimum sample of CNT/GNF hybrid nanocomposite was further tested by investigating its effect upon addition of metal oxides (MO) including zinc oxide (ZnO) and iron oxide (Fe2O3). Varying amount of MO ranging from 5-40 wt % was impregnated into the CNT/GNF nanocomposite, to form CNT/GNF/MO ternary composites via hydrothermal method. Field emission scanning electron microscopy and transmission electron microscopy shows the random entanglement of CNTs on the GNFs surfaces, and the random attachment of MO on the sidewalls of CNT/GNF hybrid. Raman spectroscopy analysis depict the enhanced ID/IG ratios, which attributed to disorder and defects. CNT/GNF sample was found to be thermally stable as much as its individual components, and the thermal stability were increased with the addition of ZnO and Fe2O3. In terms of electrochemical analysis, the combination of CNTs and GNFs was proved to be better compared to its individual component. Through cyclic voltammetry analysis, the specific capacitances (Cs) of CNT/GNF hybrid nanocomposites was found to be as high as 173 Fg-1 with 20% of CNT addition shows the optimum performance. For CNT/GNF/ZnO sample, it was found that the increased weight percentage of ZnO addition enhanced the supercapacitive performance. 40 wt % ZnO addition was determined to produce the best Cs value, 298 Fg-1. On the other hand, CNT/GNF/Fe2O3 revealed a comparable Cs value at 30 wt % Fe2O3, which found to be 290 Fg-1. In brief, this research has demonstrated that the synergistic effect between novel CNT/GNF hybrid nanocomposites and metal oxides (ZnO and Fe2O3) possess a great potential in energy storage applications.